A ocupação urbana Nova Santa Marta, Santa Maria/RS, pelas narrativas das lideranças femininas do movimento nacional de luta pela moradia - Ziegler, Ana Justina da Fonseca (2018)
This research addresses how the disorganized and excludable Brazilian urbanization process was responsible for urban problems of a social and economic order due to lack or production of unequal urban planning. In Santa Maria / RS, occupations of urban land become a means of housing for individuals with large families and precarious financial conditions. Nova Santa Marta is an irregular occupation that completed 26 years of struggle for urban land deed in the year 2017. Due to this irregularity, residents in this area are affected by social exclusion that denies their basic rights and impairs the quality of life population. The National Movement for Housing Denounces the regularization of this occupation so that its basic rights are guaranteed. Among the members of this movement are the four female leaders who play an important role in this struggle for land, since, brave, they face innumerable adversities in order to seek a life worthy of a citizen's quality. According to this perspective, the present work aims to understand the female protagonist in the production of the urban space of the occupation of Santa Marta, in Santa Maria / RS, by the bias of the land tenure struggles of women included in the National Movement for Struggle for Housing (MNLM). The methodology used will be the action research that uses social cartography as a tool to construct narrative maps of these leaderships, thus, it will be possible to understand the articulation between the problem of land ownership and the construction of housing.